2021
DOI: 10.1111/tbed.14294
|View full text |Cite
|
Sign up to set email alerts
|

PCV3 in Thailand: Molecular epidemiology and relationship with PCV2

Abstract: Porcine circovirus type 3 has been circulating throughout the world and since their first report, various clinical signs and disease developments have been documented.The virus is similar to the closely related PCV2 and is associated with several clinical signs called porcine circovirus-associated diseases (PCVAD). PCV2 or PCV3 is occasionally reported with clinical signs such as PDNS, respiratory signs and reproductive failure. Retrospective research conducted in Thailand revealed that both PCV2 and PCV3 have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Several studies have previously shown that PCV3 has spread widely around the world, infecting mainly domestic pigs [11,12,16,17,[25][26][27]. This virus has also been shown to have high prevalence in wild boars in Germany [12] and Sardinia [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have previously shown that PCV3 has spread widely around the world, infecting mainly domestic pigs [11,12,16,17,[25][26][27]. This virus has also been shown to have high prevalence in wild boars in Germany [12] and Sardinia [25].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, PCV3 can be divided into at least three clades (PCV-3a, PCV-3b and PCV-3c) based on evolutionary analysis of cap genes [11]. After the first report of PCV3 infection in the United States [7], its prevalence was determined in pigs suffering from clinical digestive or respiratory diseases in several other countries, including Germany [12], Korea [13], Sweden [14], China [15], Russia [16] and Thailand [17]. However, to date, no epidemiological study of PCV3 has been conducted with healthy pigs as a control group on the same farm.…”
Section: Introductionmentioning
confidence: 99%
“…Porcine circovirus 3 (PCV3) and porcine circovirus 4 (PCV4) are two newly emerging viruses in the swine industry, first reported in 2016 and 2019 [ 6 , 7 ]. Reports of co-infection of PCV2 with these two relatively new PCV species have surfaced, with the clinical implication of their co-existence in the swine host still being debated [ 85 , 86 , 87 , 88 ]. PCV3-positive clinical samples were frequently found to be co-infected with PCV2 with co-infection rates of 27.6% to 69.74%, suggesting the common occurrence of mixed PCV2 and PCV3 infection [ 86 , 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCV3 can be detected in pigs of different ages and causes clinical symptoms similar to those caused by PCV2. PCV3 infection can cause several clinical-pathological outcomes, such as respiratory disease, digestive disorders, congenital tremors, rectal prolapse, reproductive problems, and multisystemic inflammation, which are no less harmful to the pig industry than PCV2 [ 16 ]. However, the transmission characteristics of PCV3 in infected pigs are unclear.…”
Section: Introductionmentioning
confidence: 99%